ALTERNATIVE APPROACH TO THE METHODOLOGY OF ECOLOGICAL NORMALIZATION - Galina A. Oboldina (Водное хозяйство России: проблемы, технологии, управление)
The paper considers legal, regulatory/methodical, and scientific foundations of the system of ecological normalization of negative impacts caused by economic activities upon water environment by setting norms of quality and permissible impact. The developed system is represented by a combination of methodological provisions and instruments based on the analysis of the best available techniques in the sphere of monitoring data processing, the use of linear trends of the compressed characteristics, and indirect unified assessment of negative impacts as responses to any kind of economic activities. To provide experts with an objective toolbox and specified provisions we have developed a package of water/protective standards to support assessment of the water quality depletion, water systems degradation, actual and permissible anthropogenic load, and solution of other water/environmental problems. Approval of standardized algorithms of expert actions based on the impact monitoring data gives grounds for possible ecologization of the Water Code in order to assess the aquatic systems safety and to implement the state regulatory function of natural resources protection.